Let $X = (X_1, X_2, . . . , X_n)$ be a random sample from $Poisson(\theta)$. Use the factorization theorem to find a sufficient statistic $T(X)$ and then use the formal definition of sufficiency to confirm that $T(X)$ is sufficient.

So the factorization theorem states that if our $ f_\mathbf x(\mathbf x\mid\theta) = g(T;\theta)h(\mathbf x),$ then our sufficient statistic can be found through $T(X)$.

In this particular case, the joint pdf : $f_\mathbf x(\mathbf x\mid\theta) = \prod_{i=1}^{n} \frac{e^{-\theta}\theta^{x_i}}{x_i!} = e^{-n\theta} \theta^{\sum_{i=1}^nx_i} \prod_{i=1}^{n}\frac{1}{x_i!}$, with $T(X) = \sum_{i=1}^nx_i$ being our sufficient statistic.

What I don't understand is the second part where we use the formal definition to prove the statistic is sufficient ie to show $f_\mathbf x(\mathbf x\mid T=t)$ is independent of $\theta$.

We use $f_\mathbf x(\mathbf x\mid \sum_{i=1}^nx_i=t)$ = $\frac{f_\mathbf x,_{\sum_{i=1}^nx_i}( x, t)}{f_{\sum_{i=1}^nx_i}(t)}$, but I don't understand how to obtain $f_{\sum_{i=1}^nx_i}(t)$.

In the solutions, they use the fact that $\sum_{i=1}^nx_i \sim Poisson(n\theta) \implies f_{\sum_{i=1}^nx_i}(t) = \frac{e^{-n\theta}(n\theta)^t}{t!}$, but I don't understand how they arrived to this point, nor do I understand how they found $\sum_{i=1}^nx_i \sim Poisson(n\theta) $ either. Can someone help me?

  • 2
    $\begingroup$ Sum of n independent poisson rvs each with parameter h is poisson with parameter n*h. $\endgroup$
    – PeterR
    Nov 5, 2014 at 17:53
  • $\begingroup$ Searching our site turns up many threads in which these relationships among Poisson variables are derived: visit stats.stackexchange.com/search?q=sum+poisson+random+variable. $\endgroup$
    – whuber
    Nov 8, 2014 at 20:29

1 Answer 1


First you need to show that $\sum_{i=1}^nX_i \sim Poisson(n\theta)$. This can be done by showing that the sum of the $X_i$'s has the same MGF of a poisson random variable. Recall that for a poisson random variable $X \sim Poisson(\theta)$, its MGF is $M_x(t) = \exp\bigl(\theta(e^t - 1) \bigl)$.Since we have iid random variables, the MGF of $T = \sum_{i=1}^n X_i$ is thus $$ M_T(t) = M_{\sum_{i=1}^n X_i} (t) = M_{X_1}(t)M_{X_2}(t)\dots M_{X_n}(t) = \exp\bigl(n\theta(e^t - 1) \bigl). $$ This is exactly the MGF of a poisson random variable with parameter $n\theta$. Therefore, $$T = \sum_{i=1}^n X_i \sim Poisson(n\theta).$$

Knowing the above result makes it easy to show $f_\mathbf x(\mathbf x\mid T=t)$ is independent of $\theta$, as following.

\begin{align} f_\mathbf x(\mathbf x\mid T=t) &= \frac{f_\mathbf x(\mathbf x, \,T=t)}{f_\mathbf x(T=t)} \\ &= \frac{e^{-n\theta} \theta^t \prod_{i=1}^{n}\frac{1}{x_i!}}{e^{-n\theta} (n\theta)^t \frac{1}{t!}} \\ &= \frac{\prod_{i=1}^{n}\frac{1}{x_i!}}{n^t \frac{1}{t!}}. \end{align} And this is independent of $\theta$.

  • $\begingroup$ I really like the fact that you used the MGF to help us find the distribution for sum(xi). Hadn't thought of that before. Thank you very much for this :) $\endgroup$ Nov 10, 2014 at 10:54

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service and acknowledge you have read our privacy policy.

Not the answer you're looking for? Browse other questions tagged or ask your own question.